A study on the impact of gross domestic product (GDP), interest rate, inflation rate and exchange rate towards foreign direct investment (FDI) inflows in Malaysia / Nurhidayah Azman - Azman, NurHidayah (Faculty of Business and Management, 2014)
Foreign direct investment (FDI) inflows are important for the economic contribution in Malaysia. The factors that affecting the FDI is important in explaining the economic performance of Malaysia. The result identified several significant variables in the factors that affect the FDI inflows including Gross Domestic Product (GDP), interest rate, inflation rate and exchange rate. The study is based on time series data analysis for the 30 years starting from 1984 until 2013. The area of study is about Malaysia. In the research, the dependent variable is FDI inflows in Malaysia. Meanwhile, the independent variables are GDP, interest rate, inflation rate and exchange rate. Therefore, the purpose of the study is to determine the impact of GDP, interest rate, inflation rate and exchange rate towards FDI inflows in Malaysia.